Rabbit Cells Expressing Human CD4 and Human CCR5 Are Highly Permissive for Human Immunodeficiency Virus Type 1 Infection - Speck, Roberto F. (American Society for Microbiology, 1998)
To evaluate the feasibility of using transgenic rabbits expressing CCR5 and CD4 as a small-animal model of human immunodeficiency virus type 1 (HIV) disease, we examined whether the expression of the human chemokine receptor (CCR5) and human CD4 would render a rabbit cell line (SIRC) permissive to HIV replication. Histologically, SIRC cells expressing CD4 and CCR5 formed multinucleated cells (syncytia) upon exposure to BaL, a macrophagetropic strain of HIV that uses CCR5 for cell entry. Intracellular viral capsid p24 staining showed abundant viral gene expression in BaL-infected SIRC cells expressing CD4 and CCR5. In contrast, neither SIRC cells expressing CD4 alone nor murine 3T3 cells expressing CCR5 and CD4 exhibited significant expression of p24. These stably transfected rabbit cells were also highly permissive for the production of virions upon infection by two other CCR5-dependent strains (JR-CSF and YU-2) but not by a CXCR4-dependent strain (NL4-3). The functional integrity of these virions was demonstrated by the successful infection of human peripheral blood mononuclear cells (PBMC) with viral stocks prepared from these transfected rabbit cells. Furthermore, primary rabbit PBMC were found to be permissive for production of infectious virions after circumventing the cellular entry step. These results suggest that a transgenic rabbit model for the study of HIV disease may be feasible.